2019
DOI: 10.3390/nu11050963
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Potential of Partially Hydrolyzed Guar Gum against Acute Alcohol-Induced Liver Injury in Vitro and Vivo

Abstract: Natural polysaccharides, particularly galactomannans, are potential candidates for treatment of alcoholic liver diseases (ALD). However, applications are restricted due to the physicochemical properties associated with the high molecular weight. In this work, guar gum galactomannans were partially hydrolyzed by β-mannanase, and the molecular mechanisms of hepatoprotective effects were elucidated both in vitro and in vivo. Release of lactate dehydrogenase and cytochrome C were attenuated by partially hydrolyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 49 publications
(89 reference statements)
1
7
0
1
Order By: Relevance
“…Collectively, this perturbed redox status and hepatic inflammation led to hepatotoxicity via increased release of cytochrome C and activation of the apoptotic signaling cascade (Namachivayam and Valsala Gopalakrishnan 2021 ). This was supported by the reported increase in BAX to BCL2 ratio and caspase-3 activity in ethanol-fed mice both in our study and previous works (Wu et al 2019 ). On the contrary, BAs exerted a notable anti-apoptotic activity in ethanol-fed mice, evidenced by restriction of caspase-3 activity and BAX/BCL2 ratio, which comes in agreement with recent research on BAs’ antiapoptotic properties in various injury models (Ahmed et al 2020 ; Rajabian et al 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Collectively, this perturbed redox status and hepatic inflammation led to hepatotoxicity via increased release of cytochrome C and activation of the apoptotic signaling cascade (Namachivayam and Valsala Gopalakrishnan 2021 ). This was supported by the reported increase in BAX to BCL2 ratio and caspase-3 activity in ethanol-fed mice both in our study and previous works (Wu et al 2019 ). On the contrary, BAs exerted a notable anti-apoptotic activity in ethanol-fed mice, evidenced by restriction of caspase-3 activity and BAX/BCL2 ratio, which comes in agreement with recent research on BAs’ antiapoptotic properties in various injury models (Ahmed et al 2020 ; Rajabian et al 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Levels of hepatotoxicity biomarkers LDH, ALT, and AST correlate with hepatocyte membrane integrity and organelle damage ( 25 ). Thus, to further evaluate the protective effect of OEB, LDH, ALT, and AST levels in each experimental group were quantified.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our findings, Bozkurt et al (2016) revealed that the usage of yeast cell wall MOS to the diet of laying hens has no significant effect on MDA content in the liver. Another report involving acute alcohol-intoxicated mice found that partially hydrolyzed guar gum had a significant effect on the reduction of MDA content in the serum (Wu et al, 2019). Unfortunately, in the same tissue or organ, the scavenger roles of these antioxidative enzymes for preventing oxidative damage did not play a significant role in reducing MDA content.…”
Section: Discussionmentioning
confidence: 99%